Constraining the annual groundwater contribution to the water balance of an agricultural floodplain using radon: The importance of floods. Issue 1 (20th January 2017) - Webb, Jackie R.; Santos, Isaac R.; Robson, Barbara; Macdonald, Ben; Jeffrey, Luke; Maher, Damien T.
Abstract: The water balance of drained floodplains is highly dynamic with complex groundwater–surface water interactions operating over varying spatial and temporal scales. Here we hypothesize that the majority of groundwater discharge will follow flood events in a modified wetland. To test this hypothesis, we developed a detailed water balance that quantifies the contribution of groundwater discharge to the annual water budget of an extensively drained agricultural floodplain. A clear relationship between surface water radon measurements and groundwater level indicated alternating connection–disconnection dynamics between the drains and shallow groundwater. This relationship was used to develop a radon mass balance to quantitatively model groundwater discharge continuously throughout the year. Groundwater discharge varied by four orders of magnitude over the study period, with daily average rates ranging from 0 to 27, 200 m 3 d −1, peaking just a few hours after floods receded. Flood events occurred only 12% of the time yet contributed 72–76% of the total groundwater discharge. During flood recession periods, aerial groundwater discharge rates reached up to 325 cm d −1 which were some of the highest rates ever estimated. We proposed that the high drainage density of this site (12.4 km constructed drains km −2 catchment area) enhanced groundwater discharge during wet periods due to increased connectivity with the soil. Overall, groundwater discharge contributed 30–80% to the total surface water discharge. This study offers insight into the dynamic behavior of groundwater within an extensively drained floodplain, and the importance of capturing flood events to quantify total groundwater contribution to floodplain water balances. Key Points: Combined radon and groundwater level observations allowed the construction of a detailed groundwater budget. Flood recession periods contributed 72–76% to annual groundwater discharge. Groundwater discharge contributed 30–80% to total surface discharge.